PENERAPAN EXCEL AKUNTANSI DALAM PENYUSUNAN LAPORAN KEUANGAN UMKM TRIJAYA FURNITURE - Wardiningsih, Reny; Dewi, Resty Yusnirmala; Umam, Khaerul; Rahayu, Nila; Ferdaus, Nadia Nuril (Jurnal Abdimas Musi Charitas, 2024)
Micro, Small and Medium Enterprises (MSMEs) have an important role in economic development in Indonesia. Trijaya Furniture, a manufacturing MSME producing finished goods since 2008, faces challenges in preparing well-structured financial statements. This issue impacts trust and accessibility for external parties, such as financial institutions and investors. This community service activity aims to implement Excel Accounting as a tool for preparing financial statements to enhance financial management quality. The implementation method consists of three stages: Observation, to understand needs and challenges,  Intensive training, focusing on creating Excel-based financial statements aligned with standards, and Evaluation and monitoring of training outcomes. The results show an improvement in MSME practitioners' ability to prepare accurate and organized financial statements, along with increased trust from external partners.